Comparative medicine : disorders linking humans with their animals - Jensen-Jarolim, Erika (Springer, 2017)
This book highlights the most significant diseases for humans and their dogs, cats and horses. The examples discussed, which include allergies, osteoporosis, cancer and many more, illustrate that humans and their companion animals may in fact develop similar diseases. The reader - whether expert or interested lay - can thus directly compare between human and animal patients. The animal patient thereby represents a natural disease model, which besides the experimental models, is urgently needed to improve the therapeutic options for both humans and animals.- Resumé vydavatel
Keywords: experimentální medicína; nemoci domácích zvířat; experimental medicine; domestic animals diseases; elektronické knihy; srovnávací studie; electronic books; comparative studies